Pengaruh Budaya Layanan, Customer Value, Dan Brand Equity Terhadap Loyalitas Nasabah Produk Pembiayaan Pensiun Di Bank Syariah Indonesia KC Bengkulu Sudirman - Ella Ariyani; Idwal B; Aan Shar (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to determine the influence of service culture, customer value andbrand equity on customer loyalty for pension financing products at Bank Syariah IndonesiaKC Bengkulu Sudirman. This research uses quantitative methods with multiple linearregression analysis methods. The samples used were 110 samples determined by purposivesampling. The results of this research show that simultaneously service culture, customervalue and brand equity have a positive and significant effect on customer loyalty for pensionfinancing products at Bank Syariah Indonesia KC Bengkulu Sudirman, this is proven by thecalculated F value of 66,541 and a significant value of 0.000 < 0.05. Partially 1) serviceculture has a positive and significant effect on customer loyalty with a significant value of0.000 < 0.05. 2) customer value has a positive and significant effect on customer loyalty witha significant value of 0.000 < 0.05. 3) brand equity has a positive and significant effect oncustomer loyalty with a significant value of 0.000 < 0.05